Insights Into Host Cell Cytokines in Chlamydia Infection - Xiang, Wenjing; Yu, Nanyan; Lei, Aihua; Li, Xiaofang; Tan, Shui; Huang, Lijun; Zhou, Zhou (Frontiers in Immunology, 2021)
Chlamydial infection causes a number of clinically relevant diseases and induce significant morbidity in human populations. Immuno-inflammatory response is very important for clearing Chlamydia infection. Chlamydia infection stimulates host cells to produce a large number of cytokines that regulate host immune responses against Chlamydia. But inappropriate response would lead to uncontrolled secretion of cytokines, resulting in uncontrolled inflammation and changes in host or bacterial metabolism. This would not only be helpful for microbe’s survival, but also result in wound healing delay and formation of severe tissue damage. Here, we summarized the main work of chlamydial researches related to cytokines, especially the level, the role and the involved mechanism of various cytokines in the process of Chlamydia infection. It is useful for systematic understanding the pathogenic mechanism of Chlamydia, and can help to develop better strategies for the treatment and prevention of chlamydial infection.